USE OF COMPRESSION GARMENT IN THE TREATMENT OF MALIGNANT LYMPHEDEMA IN A PATIENT WITH RECURRENT BREAST CANCER: CASE REPORT - Campanholi, Larissa Louise; Baiocchi, Jaqueline Munaretto Timm; Mansani, Fabio Postiglione (Mastology, 2019)
Introduction: Malignant lymphedema is a rapidly progressive condition, and its treatment is a major challenge. Objective: To demonstrate the benefit of using compression garments in reducing limb volume and improving the symptoms of a patient with malignant lymphedema with recurrent breast cancer. Case report: A 67-year-old woman, diagnosed with a 2.3 cm, triple negative, invasive ductal carcinoma in the left breast, submitted to quadrantectomy with axillary dissection (T2aN1bM0). The patient developed benign lymphedema after eight years of surgery, but only started complex decongestive physiotherapy three years after the diagnosis, presenting an important improvement. The following year, the patient returned with complaints of worsening lymphedema. At the examination, there was an expressive volume increase and areas of vascular alteration in the left upper limb (LUL) and in the anterior quadrant of the thorax. The exams confirmed axillary vein thrombosis due to tumor obstruction. Lymphoscintigraphy showed unsatisfactory lymphatic drainage. As a last treatment option, the use of LUL low elastic compression garment was adopted, after poor success after the use of multi-layered compression bandages. LUL volume was 6,158.1 mL prior to using the garment. After ten days of continuous use, the volume decreased to 5,174.2 mL. In the last evaluation, the volume was 4,510.8 mL, presenting a reduction of 1,647.3 mL (26.7%). The patient developed acute respiratory failure caused by pleural metastasis, and died. Conclusion: The compression garment provided benefits such as significant improvement in the feeling of heaviness in the limb due to the reduction of volume and in the ease of putting on and taking off the garment in or make the hygiene, when compared to the multilayer compression bandages. Other advantages were the reduction of costs and the promotion of well-being.